2018
DOI: 10.1007/s40430-018-0963-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of welding characteristics using three-dimensional finite element simulation and experimentation for FSW of aluminum 6061

Abstract: Aim of this study is to introduce numerical 3D finite element method (FEM) simulation to study characteristics of friction stir welding. A coupled experimental and numerical simulation study was carried out to study the effect of process parameters on welding characteristics for friction stir welding of aluminium 6061. As per Box-Behnken design, 15 experiments have been conducted on aluminium 6061 plates at three levels of spindle speed, tilt angle and tool pin diameter. Experimental results of tool vibration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently, many research studies are inclined toward solidstate welding which normally performs below the melting point of alloys includes friction stir welding (FSW), diffusion welding, pressure bases solid-state welding and brazing (Zn-based filler) as a solution for the above-stated problem [7]. One study utilized FSW to join AA6061 with magnesium alloy in order to minimize the formation of the brittle intermetallic compound at the interface.…”
Section: Page 2 Of 13mentioning
confidence: 99%
“…Recently, many research studies are inclined toward solidstate welding which normally performs below the melting point of alloys includes friction stir welding (FSW), diffusion welding, pressure bases solid-state welding and brazing (Zn-based filler) as a solution for the above-stated problem [7]. One study utilized FSW to join AA6061 with magnesium alloy in order to minimize the formation of the brittle intermetallic compound at the interface.…”
Section: Page 2 Of 13mentioning
confidence: 99%
“…Up to now, much work has been done on the finite element method of the FSW process to study the thermal and mechanical properties, material flow velocity, viscosity profile, etc. 1115 Nandan et al 16 investigated the numerical analysis to analyze the effect of temperature distribution, material flow, and cooling rate on microstructure properties during the FSW. They indicated that the shape and microstructure of the stir zone were affected by the aforementioned factors.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, FSW is applicable for joining low melting point materials such as aluminium alloys, copper and magnesium. The effects of the process parameters on the microstructure [1][2][3], thermal and mechanical properties of aluminium alloys [4][5][6][7] have been studied by several researchers. The feasibility of joining copper and dissimilar materials such as aluminium and copper has also been studied to investigate the optimum machining parameters on the mechanical properties of the materials [8,9].…”
Section: Introductionmentioning
confidence: 99%